MASTERING THE MIX: A MODERN GUIDE TO BUDGETING AND MANAGING MULTI-CHANNEL MARKETING - Bhayu Bomantara; Lukmanul Hakim; Dahrul Aman Harahap (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
In an era of channel proliferation and complex customer journeys, determining the optimal allocation of marketing budgets across diverse platforms has become a central strategic challenge. This study examines the contemporary practices and analytical frameworks for budgeting and managing multi-channel marketing to maximize return on investment. The objective is to develop an integrated model for dynamic budget allocation, cross-channel performance measurement, and agile management in a fragmented media landscape. Employing a mixed-methods approach, the research analyzed financial data from 15 enterprises and conducted 45 interviews with marketing and finance executives. The results reveal that organizations utilizing a test-learn-allocate cycle, supported by unified measurement and agile processes, achieved 22% higher marketing efficiency than those relying on historical allocation. The discussion focuses on the shift from fixed annual budgets to flexible investment frameworks, the critical role of incrementality testing, and the organizational structures that enable effective multi-channel orchestration. It is concluded that mastering the modern marketing mix requires abandoning siloed channel management in favor of a holistic, data-driven, and continuously optimizing approach to resource allocation.